Analyzing and optimizing wi-fi access point performance / Fadhli Dzul Hilmi Bin Mohd Fauzi - Mohd Fauzi, Fadhli Dzul Hilmi (2013)
Wireless technology has improved to help the user to simplify networking by reducing the amount of cables uses and connecting multiple devices to simultaneously share and connects devices with each other. It is now common that wireless networking applies into many infrastructures and buildings for the connection of the clients to the internet or sharing information or data with each other. This consequently has brought pros and cons to the clients of wireless network. A Wireless Local Area Network (WLAN) is a type of Local Area Network (LAN) that uses high frequency radio waves to communicate and transmit data. A reliable WLAN network should satisfy the needs of the clients and give the best performance especially data sharing within the network thus Access Points (AP) is used in an area. Even with the usage of APs, propagation inside building suffers from interference and overlap channel. Hence it is necessaiy to identify the quality of the wireless connection and how to improve the communication through WLAN by positioning the AP. Therefore, in this paper, Analyzing and Optimizing WiFi Access Point Performance has been proposed to analyze a study case with APs network problems and its performance. The case study area used in the research is in the Intelek Building located in the Universiti Teknologi MARA, Terengganu.